The influence of sustainable design features on indoor environmental quality satisfaction in Turkish dwellings. (3rd May 2016) - Afacan, Yasemin; Demirkan, Halime
Abstract : The aim of this paper is to explore the influence of sustainable design features on occupants' satisfaction levels with indoor environmental quality (IEQ) aspects in three types of dwellings. Satisfaction level was investigated through a field survey with 240 participants, in apartments, row and detached houses in Turkey. Satisfaction level was explored in terms of overall satisfaction with IEQ, with the efficiency of daily living activities and with sleeping quality. Satisfaction level was also investigated regarding the dwellings' thermal, ventilation, lighting, sound level and moisture qualities. The findings indicate that the existence of exterior insulation, a thermostat, light dimmers and control of daylighting systems through operable windows have high impacts on the satisfaction level of occupants living in all three types of dwellings.